A comparison of spring body condition, maturation status, and diet in the European sardine, Sardina pilchardus (Teleostei: Clupeidae) from contrasting environments off the Moroccan Atlantic coast. Issue 6 (8th August 2020) - El Mghazli, Hayat; Mounir, Abdelaziz; Znari, Mohammed; Naimi, Mohamed; El Ouizgani, Hassan; Aourir, Mohamed
ABSTRACT: The bulk of marine fish production in Morocco comprises small pelagic with a large predominance of the European sardine Sardina pilchardus . Information on feeding intensity and diet composition of small pelagic fish are of great importance for understanding species ecology and life-history traits and fisheries management. In the present study, we compared body condition, sexual maturation, feeding intensity and diet composition (stomach content analysis) in sardines from contrasting fishing environments representative of the three Moroccan Atlantic stocks (North: Larache; central: Safi; and south: Dakhla) in spring 2016. The body condition factor increased from north to south and varied inversely with gonado- and hepato-somatic ratios. The feeding intensity was low in Larache and Dakhla and higher in Safi, related to the reproductive status. Sardines are generalist feeders selecting primarily zooplankton (copepods and cnidarians) in Larache and phytoplankton (diatoms and dinoflagellates) in Dakhla and Safi. However, based on carbon content, sardines from the three locations are rather zooplanktivorous. Great similarity in numerical specific abundance was found between the diets in sardines from Dakhla and Safi, which are areas of high phytoplankton productivity in the spring. In contrast, there was a low similarity in diet between sardines from Dakhla and Larache in relation to the low productivity and differences in sexual maturation of sardines from the latter. We concluded that in spring, the feeding intensity and diet composition of sardines depend on their reproductive status and ecosystem productivity, which affect their body condition.